Impact of the COVID-19 pandemic on the codification of China’s civil code - Zhai, Gaoyuan; Liu, Xiaochang (Frontiers in Public Health, 2024)
The COVID-19 pandemic has spread widely around the world since 2019, wreaking havoc on social order in a global context. In China, the pandemic has not only provided new challenges to the government's capacity, it has also provided new issues for the Civil Code that is being compiled. China's Civil Code was promulgated on May 28, 2020, and compared to the draft Civil Code published on December 16, 2019, the official Civil Code added, deleted, and adjusted some provisions, which included five provisions that were relevant to the COVID-19 pandemic. The Civil Code was enacted at the time of the COVID-19 pandemic, which led to some of its provisions affected by the COVID-19, and the "COVID-19 provisions" not only provided legitimacy for the prevention and control of the pandemic, but also improved China's system of governance of public health emergencies. However, this paper holds that the "COVID-19 provisions" of China's Civil Code aren't faultless, and the rationality of some provisions still needs further discussion.